PERBEDAAN KADAR TRIGLISERIDA PADA DARAH HEMOLISIS DAN NON HEMOLISIS - Layalial Mukharomah; Apriani Apriani (Jurnal Medical Laboratory, 2022)
Triglycerides are the main fats in food that play a role in the transport and storage of fat in the body. Increased levels of triglycerides within the normal threshold are called hypertriglycerides and also hyperlipidemia. Examination of triglycerides with hemolysis blood can cause high triglyceride levels rather than non hemolis. This study aims to find out there are significant differences in the results of Triglyceride examination using blood hemolysis and non hemolysis. This study was carried out by the ENZIMATIC COLORIMETRY (GDO-PAP) method which was immediately examined using hemolysis and non hemolysis blood. This study was conducted at the Grogol Petamburan District Health Center Laboratory in September to November 2018. The results of the examination of triglyceride levels with non-hemolytic blood in this study showed a mean value of triglyceride levels with hemolis 187 mg / dl and with hemolytic blood average values ​​- the average is 261 mg / dl. and the results of the Wilcoxon Test show the results of P value = 0.00 (P value <0.05). The data conclude that there are significant differences between triglyceride levels and non hemolysis and hemolysis.